FoxO3a: capture the bond between magnesium and diabetic kidney disease - Chen, Taoran; Sun, Miao; Zhou, Qi; Xu, Jiancheng (Frontiers in Endocrinology, 2025)
Hyperglycemia in Diabetic Kidney Disease (DKD) induces excessive accumulation of reactive oxygen species (ROS) through various pathways, leading to oxidative stress, ferroptosis, and mitochondrial dysfunction, which collectively contribute to kidney damage. Currently, the treatment of DKD remains a significant challenge. Magnesium, an essential mineral, has emerged as a promising therapeutic agent for DKD due to its anti-inflammatory and antioxidant properties. Magnesium has been shown to alleviate renal fibrosis, maintain tubular integrity and function, improve endothelial cell function, and regulate renal hemodynamics. As a cofactor of antioxidant enzymes, Magnesium directly scavenges ROS and enhances the expression of antioxidant proteins. This review explores the relationship between Magnesium and DKD, examining how Magnesium mitigates oxidative stress through the PI3K/AKT/FoxO3a pathway, inhibits ferroptosis in renal tubular epithelial cells via the AMPK/FoxO3a/Nrf2 pathway, and reduces autophagy and apoptosis, thereby delaying DKD progression. The review further discusses how Magnesium regulates the pivotal FoxO3a protein, a transcription factor with antioxidant properties, leading to the prevention of DKD, and proposes Magnesium supplementation as a potential clinical strategy for alleviating DKD, offering a new therapeutic approach for its treatment.